(untitled) (Bioagro, 2023)
Information regarding the productive potential of Hibiscus sabdariffa in different environments and planting densities is scarce. The objective of the study was to evaluate the effect on the calyxes of the Alma Blanca, Escarlata, Quinba and Sudán varieties, in various environments (Guerrero, Oaxaca, Puebla and Quintana Roo States) and densities of 15625, 20833, 31250 and 41666 pl ha-1. A randomized block design, with four repetitions, and 4x4x4 factorial arrangement of the treatments was used. The results indicate that at 200 days after transplant more than 85 % of mature calyxes (with red color and separation of bracts) were obtained. The Sudan variety developed calyxes with a larger diameter and dry weight per calyx (7.42 cm and 2.61 g, respectively), and up to 20 seeds per fruit in Quintana Roo at 15625 pl·ha-1. The pH (2.88) and acidity (24 %) of the extracts were higher in Alma Blanca, in Oaxaca at 41666 pl·ha-1; while total soluble solids (85 %) and anthocyanins (4.0 mg·g-1) were higher in Sudan, in Oaxaca at 15625 pl·ha-1. The most important anthocyanins found were delphinidin-3-sambubioside and cyanidin-3-sambubioside, with 62.56 and 25.49 %, respectively; these compounds were obtained in Sudan, in Guerrero at 15625 pl·ha-1. It is concluded that the variety, the production environment, and the plant density influence the quality and chemical composition of the calyxes.